2017
DOI: 10.1155/2017/9565430
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Walking among Middle-Aged and Older Overweight and Obese Adults: Sociodemographic, Health, and Built Environmental Factors

Abstract: Background This study examined the association between selected sociodemographic, health, and built environmental factors and walking behaviors of middle-aged and older overweight/obese adults. Methods Subjective data were obtained from surveys administered to community-dwelling overweight/obese adults aged ≥50 years residing in four Texas cities from October 2013 to June 2014, along with objective data on neighborhood walkability (Walk Score™). Multivariate logistic regression identified factors predicting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
13
0
2
Order By: Relevance
“…One quarter of the studies (n = 9) tested the mediating role of demographic, psychosocial, functional, behavioral, and/or environmental features on the association between NE and PA [ 125 , 127 , 128 , 130 132 , 144 146 ]. Other studies tested whether associations between NE and PA were moderated by age, sex or education, driving status, crime and safety or objective walkability [ 82 , 121 , 126 , 147 , 148 ]. The target of one study [ 149 ] was to examine the value of PA as a moderating element for somatic health.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One quarter of the studies (n = 9) tested the mediating role of demographic, psychosocial, functional, behavioral, and/or environmental features on the association between NE and PA [ 125 , 127 , 128 , 130 132 , 144 146 ]. Other studies tested whether associations between NE and PA were moderated by age, sex or education, driving status, crime and safety or objective walkability [ 82 , 121 , 126 , 147 , 148 ]. The target of one study [ 149 ] was to examine the value of PA as a moderating element for somatic health.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to PA, sociodemographic factors (i.e., sex and age) were the most frequently examined moderators at the individual level. At the NE level, objectively measured walkability [ 148 ], a Walkscore [ 126 ], buffer sizes [ 137 ] and primary type of buildings in the neighborhood [ 145 ] were assessed. However, the majority of studies (n = 19) examined self-reported features such as mental health status [ 127 , 131 ], perceived PA [ 40 , 125 , 127 ], perception of crime and safety [ 145 147 ], perceived NE [ 130 , 131 ], social cohesion/support [ 127 , 132 , 144 , 146 ], health/medical condition or functional limitations [ 132 , 149 ], self-efficacy [ 132 ], perceptions of proximity [ 153 ] and self-reported park visits [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscale, or neighborhood level, infrastructure includes solutions such a maintained footpaths [35], availability of street lights [35], presence of sidewalks/protected walkways [36,37], quality of street crossings [20], street connectivity [39], recreational facilities [28], as well as rest stops and benches [35]. Microscale changes not only increase walkability [41], but have also been shown to have a positive impact on walking for travel in older adults [20,28,34,35,36,37,40,42]. Microscale infrastructure also positively affects neighborhood aesthetics, which has been shown to increase leisure and utilitarian walking [34,40,42].…”
Section: Resultsmentioning
confidence: 99%
“…Environmental interventions focused on the built environment can be a critical component that can both target social interactions and physical activity [ 39 , 40 ]. Identifying sustainable solutions—namely walkable environments that will help increase or maintain adequate levels of physical activity [ 12 , 39 , 40 , 41 , 42 ]—is critical. Potential solutions also transcend environmental solutions into behavioral interventions.…”
Section: Discussionmentioning
confidence: 99%